THE ROLE OF CONGREGATIONAL DHUHA PRAYER ACTIVITIES IN FORMING STUDENTS' SPIRITUAL CHARACTER - Hendro Juwono; Muhammad Zamroni (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study aims to analyze the role of congregational Dhuha prayer activities in shaping students’ spiritual character . The background of this research is based on the importance of developing religious character through the habituation of worship as an integral part of Islamic education. The research employed a qualitative approach with data collection techniques including observation, interviews, and documentation. The research was conducted at Anshoriyah, Parijata Wetan Village. Data were analyzed using an interactive analysis model, consisting of data reduction, data display, and conclusion drawing. The findings revealed that the implementation of congregational Dhuha prayer significantly contributes to the development of students’ spiritual character. Regular and structured worship activities foster religious values reflected in positive behavioral changes among students. The observed impacts include increased punctuality, personal responsibility, emotional calmness, politeness and social empathy, as well as enhanced awareness of worship and gratitude to Allah. Supporting factors for this activity include strong commitment from the principal and teachers, adequate mushalla facilities, and continuous guidance. Meanwhile, inhibiting factors include limited awareness among some lower-grade students and the need to strengthen worship motivation. The habituation of congregational Dhuha prayer serves as an effective strategy for strengthening students’ spiritual character and is worthy of implementation as a religious culture development program in Islamic elementary schools.